1980
DOI: 10.1088/0022-3727/13/11/022
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conduction in n-octadecane crystals

Abstract: The currents flowing along two crystal directions, viz. parallel with and perpendicular to the molecular axis, were monitored but an apparent anisotropy in the conduction properties was removed by a voltage conditioning procedure. It is concluded that n-octadecane does not show an intrinsic DC conduction process when pure, defect-free crystals are grown. The voltage step-responses of the crystals do, however, show the logarithmic time dependence which is common to a wide range of insulators and semiconductors.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

1982
1982
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The reason is primarily the lack of suitable tools for probing magnetism at very high pressures. The only extensive studies reported so far 6,7 are in the ferromagnetic semiconductor EuO. No study, however, has shown evidence for the total collapse of magnetic ordering.…”
mentioning
confidence: 97%
“…The reason is primarily the lack of suitable tools for probing magnetism at very high pressures. The only extensive studies reported so far 6,7 are in the ferromagnetic semiconductor EuO. No study, however, has shown evidence for the total collapse of magnetic ordering.…”
mentioning
confidence: 97%
“…is a dimensionless quantity, Rsh is the sheet resistance in the pentacene layer, and f is the frequency for capacitance measurement. 32,33) Equation ( 3) can be derived by assuming that the line inductance and parallel resistance in a distributed constant circuit with open termination are equal to zero. When a function g(α) is defined as…”
Section: Characteristics Of Mos Capacitorsmentioning
confidence: 99%
“…In order to eliminate the influence, it is necessary to remove the organic layer uncovered with the contact electrode. 18) Some groups have examined organic TFTs 27,28) and organic MOS capacitors [29][30][31][32][33] considering organic semiconductor areas uncovered with the contact electrode. Hamadani et al and Girolamo et al investigated the characteristics of organic TFTs using equivalent circuits consisting of distributed elements for the uncovered area.…”
Section: Introductionmentioning
confidence: 99%
“…where ϕ is the electric potential; q is the electronic charge; ε 0 is the permittivity of free space. The current I in the external circuit due to the motion of electrons and ions between the electrodes is calculated using Stato's equation [22] :…”
Section: Mathematical Model Of Gas Dischargementioning
confidence: 99%